PENDAMPINGAN SERTIFIKASI HALAL SEBAGAI UPAYA STRATEGIS DALAM MENINGKATKAN LEGALITAS DAN DAYA SAING UMKM - Khoirul Anam; Linawati; Wulan Feronika Maharani; Mohammad Irvan Bayu Saputra; Farida Nur Mudmainah Wahyuningsih; Muhammad Fatkhul Ikhwansyah; Afini Fikriyani; Amelia Putri Cahyanti; Wahyu Kukuh Prayoga; Nur Rohman Hidayat; Naufal Friza Asraful Arifin; Rimas Sadha Abdi Putra; Sofia Widiana; Linda Suciati (Abdimas IAI Ngawi, 2025)
The halal certification assistance program for Micro, Small, and Medium Enterprises (MSMEs) is a strategy to enhance business legality, consumer trust, and product competitiveness. This initiative was implemented by PPM Group 09 IAI Ngawi in Mrahu Village, Kartoharjo Sub-district, Magetan District, in collaboration with the Halal Center IAI Ngawi and the Mrahu Village Government. The method used is Participatory Action Research (PAR) with four main stages: Community Research Social Problem Diagnostic to identify barriers, Community Strategic Planning to develop mentoring strategies, Community Resource Mobilization for socialization and technical guidance implementation, and Reflection for evaluation and follow-up. The program targets three food processing MSMEs without halal certification, as well as PKK members of Mrahu Village as additional participants. As a result, all participants successfully completed the required documents and submitted their certification applications through the SiHalal BPJPH system. The face-to-face approach and technical assistance proved effective in addressing digital literacy and administrative challenges. This program is recommended for expansion through sustained collaboration among stakeholders. Keywords: Halal Certification Assistance, UMKM, Business Legality, Community Empowerment   Abstrak: Program pendampingan sertifikasi halal bagi Usaha Mikro, Kecil, dan Menengah (UMKM) merupakan strategi untuk meningkatkan legalitas usaha, kepercayaan konsumen, dan daya saing produk. Kegiatan ini dilaksanakan oleh PPM Kelompok 09 IAI Ngawi di Desa Mrahu, Kecamatan Kartoharjo, Kabupaten Magetan, bekerja sama dengan Halal Center IAI Ngawi dan Pemerintah Desa Mrahu. Metode yang digunakan adalah Participatory Action Research (PAR) dengan empat tahap utama, yaitu Community Research Social Problem Diagnostic untuk mengidentifikasi hambatan, Community Strategic Planning untuk menyusun strategi pendampingan, Community Resource Mobilization untuk pelaksanaan sosialisasi dan bimbingan teknis, serta Reflection untuk evaluasi dan tindak lanjut. Sasaran program mencakup tiga pelaku UMKM pangan olahan yang belum memiliki sertifikasi halal, serta anggota PKK Desa Mrahu sebagai peserta tambahan. Hasilnya, seluruh peserta berhasil melengkapi dokumen dan mengajukan sertifikasi melalui sistem SiHalal BPJPH. Pendekatan tatap muka dan pendampingan teknis terbukti efektif mengatasi hambatan literasi digital dan administrasi. Program ini direkomendasikan diperluas dengan sinergi berkelanjutan antar pemangku kepentingan. Kata Kunci: Pendampingan Sertifikasi Halal, UMKM, Legalitas Usaha, Pemberdayaan Masyarakat